Development, validation, and application of a fast, simple, and robust SPE-based LC-MS/MS method for quantification of angiotensin I-converting enzyme inhibiting tripeptides Val-Pro-Pro, Ile-Pro-Pro, and Leu-Pro-Pro in yoghurt and other fermented dairy products. (October 2019) - Moosmang, Simon; Siltari, Aino; Bolzer, Marie-Theres; Kiechl, Stefan; Sturm, Sonja; Stuppner, Hermann
Abstract: Dairy products are an important part of a nutritionally balanced diet as their constituents can affect the human state of health. By inhibiting the angiotensin I-converting enzyme, the tripeptides Val-Pro-Pro, Ile-Pro-Pro, and Leu-Pro-Pro can lower blood pressure. As these peptides are produced during fermentation, they are found in various dairy products like cheese, yoghurt, etc., but except for cheese only little is known about their content. To investigate how other dairy products contribute to a supply of these antihypertensive peptides, we developed and validated a fast and sensitive assay for quantification of the three tripeptides with LC-MS/MS combined with a simple protocol for extraction and SPE-purification from yoghurt, curd, or other products. Finally, the entire method was successfully applied to survey peptide concentrations in samples from local dairies and thus expands our awareness on the content of antihypertensive peptides in our food.